Divergent ECC1 effector homologs modulate host-specific virulence in cucurbit-infecting Fusarium oxysporum - Vlieger, Babette V.; Fokkens, Like; Takken, Frank L. W.; Rep, Martijn (Frontiers in Cellular and Infection Microbiology, 2025)
Fusarium oxysporum (Fo) is a soil-borne fungal pathogen that causes wilt disease in over one hundred plant species, with host-specific strains classified into formae speciales (ff. spp.). For example, Fo f. sp. melonis (Fom) only causes disease in melon while Fo f. sp. radicis-cucumerinum (Forc) can infect multiple cucurbit species. The virulence factors underlying host specificity in these cucurbit-infecting formae speciales have largely remained elusive, limiting our understanding of Fo-host interactions. A previous study identified Effector for Cucurbit Compatibility 1a (ECC1a), an avirulence protein from Fom that restricts cucumber infection when introduced into Forc. Here, we show that ECC1a is part of a previously unrecognized effector gene family, ECC1, abundantly present in strains that infect one or more cucurbit species. However, the role of this family in host compatibility is still poorly understood. Using gene knockout- and replacement strategies, we show that the ECC1 gene family contributes to virulence of both Forc and Fom on cucumber and melon. Specifically, ECC1a contributes to Fom virulence on melon and Forc virulence on cucumber. ECC1b appears to be primarily involved in Fom virulence on melon.Expression profiling reveals a potential role of ECC1 during early stages of infection, suggesting involvement in initial host colonization. Together, these findings highlight the host- and forma specialis-specific functions of ECC1 homologs in Fo pathogenicity.